Nutritional status of children from Cochabamba, Bolivia: a cross-sectional study - Cristina Masuet-Aumatell; Josep Maria Ramon-Torrell; Marta Banqué-Navarro; María del Rosario Dávalos-Gamboa; Sandra Lucía Montaño-Rodríguez
OBJECTIVE:To assess the adequacy of energy and nutritional intakes compared to recommended daily intakes (RDIs) in schoolchildren from the Cochabamba region (Bolivia) and to determine micronutrient intake distributions across different ages and genders. METHODS: This nutritional study (n = 315) was part of a larger population-based crosssectional study (the "Bolkid" survey) that collected data on schoolchildren 5-16 years old in 2010 in the Cochabamba region. Information about food intake was gathered with a semiquan-titative, food-frequency, parent-administered questionnaire about l2 months before the study. Descriptive and bivariate analyses of energy and nutrient intakes were assessed. RESULTS: For all ages studied and both genders, the average energy and micronutrient intakes were acceptable but below the requirements. The diet included high amounts of fiber, some minerals (iron, magnesium, phosphorus, potassium, sodium), and vitamins (pantothenic acid, niacin, vitamins B2, B12, C, and E), but was low in calcium and vitamin D. However, more than half the children had insufficient energy intake, and low calcium, vitamin A, and vitamin D intakes, according to RDIs adjusted for age and gender; one-third of the children had insufficient folate and magnesium intakes; and adolescent girls had low iron intakes. CONCLUSIONS: Regardless of recommendations or demographic characteristics, the vast majority of children in Cochabamba consumed insufficient energy and too little calcium, folate, magnesium, and vitamin A and D. In addition, adolescent girls consumed insufficient iron. Higher energy intake for schoolchildren through increased food availability, frequency, and size portions in daily meals should be a priority for Bolivian public health institutions.